Influence of the implant scan body modifications on trueness of digital impressions - Sema Merve Uzel; Mustafa Baris Guncu; Guliz Aktas; Hale Arikan; Natalia Reiss; Ilser Turkyilmaz (Elsevier, 2023)
Background/purpose: Effects of implant angulation on digital impression accuracy remain controversial. The purpose of this study was to assess the relationship between the alteration of implant scan bodies and the trueness of digital impressions. Materials and methods: A maxillary typodont without the right premolars and first molar was scanned with a laboratory scanner and saved as a standard triangular language (STL) file. A model from the STL file was fabricated with a 3-dimensional printer. Two implants were placed into the first premolar and first molar sites of the model, followed by the insertion of two scan bodies onto the implants. These scan bodies were divided into four test groups, based on the surface modifications. A digital impression of each typodont was made with three different intraoral scanners. An abutment was digitally seated on each implant. 120 STL files (30 for each group) of the typodont with two implants and two corresponding abutments were used for statistical analysis. Results: A total of 240 values (two implants for each typodont) were obtained after each sample (4 groups) was scanned 10 times by utilizing three intraoral scanners. The overall linear and angular discrepancies were analyzed. Group 1 showed the lowest linear discrepancy of 14.9 ± 5.4 μm while Group 4 reported the highest linear discrepancy of 137.5 ± 41.7 μm, yielding a statistical significance (P < 0.05). Conclusion: It has been concluded that the more adjustments made to the scan bodies, the greater the linear and angular deviations occur, compromising the trueness of the digital implant impression.